Preoperative counseling and quality of life of patients with ostonomy - Batalla, Mary Grace Anne P.
Patients with an ostomy are faced with physiologic and psychosocial problems relating to structural changes and altered functional health patterns following surgery. Hence, specialized care provided by stoma nurses should be aimed towards maximizing patient self-efficacy in stoma management and assisting them to eventually achieve an optimal level of well-being. However, there is scarce research on what preoperative interventions are performed by stoma nurses and how there interventions affect the quality of life (QOL) of ostomates after stoma formation. -- The study aimed to (1) determine patient factors that are associated with the QOL, (2) determine the relationship between preoperative counseling and QOL, and (3) examine how ostomates describe the domains of QOL during the early postoperative phase. -- The study utilized a cross-sectional descriptive correlational design. Purposive sampling using inclusion-exclusion criteria of patients who were at least three days post-surgical creation of fecal ostomy (n= 112) was performed. QOL was assessed using the validated Filipino version of the Stoma-QoL Questionnaire. Qualitative analysis of interview responses was employed to extract descriptions about the domains of QOL following surgery. -- Mean QOL score was 56 (SD = 10) suggesting moderate levels of QOL in the early postoperative phase. Sex, place of residence, annual family income, financial status, presence of comorbidity, and type of surgical procedure were patient factors found to be associated with QOL. Item analysis showed significant differences in responses relating to QOL based on sociodemographic-, clinical-, and hospital stay-related characteristics. There are no significant difference in the QOL scores of patients who were seen preoperatively by a stoma nurse either for stoma marking or counseling from those who were not seen at all (p = 0.84). Qualitative analysis revealed 18 patterns describing the domains of QOL in the early postoperative phase. -- Factors associated with QOL may provide value in the planning and implementation of safe and quality stoma nursing care. In particular, stoma nurses can focus on the spiritual domain of ostomates and further explore how this area can be strengthened to improve QOL levels. Future research can be aimed towards exploration of other factors not included in this study that can affect QOL, how preoperative interventions can impact QOL scores over time, and what nurse-related dimensions can positively influence the stoma experience.